Geomatics engineering ecosystem, what more to be done - Syed Ahmad Fadhli Syed Abdul Rahman,; Khairul Nizam Abdul Maulud,; Hazri Hassan,; Sharifah Nurul Ain Syed Mustorpha, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Shared Prosperity Vision 2030 (WKB2030) is one of the Malaysian government’s initiatives to achieve the goals of a developed country by the year 2030. It is one of the motivational pillars that ought to underpin state-level policymaking and development strategies with the participation of all relevant professional professions. The geomatics engineering profession is one of the country’s core prospects and has contributed to the geomatics field in Malaysia, also responding to the call of WKB2030. Unfortunately, the digitalization process is moving too fast and adaptation to current technologies is crucial to stay relevant in the industry. As a result, this study highlighted the geomatics engineering direction through previous study trend identification and the compilation of the blueprint for WKB 2030 to ensure the geomatics engineering profession strives hard in adapting and contributing to national development. To empower the geomatics engineering ecosystem, various initiatives have been emphasized with the involvement of the geomatics engineering community in implementing new measures to enhance the field’s established services by leveraging innovations developed in the context of the Fourth Industrial Revolution (IR 4.0). Lastly, this manuscript will examine, from a geomatics engineering stance, how the geomatics field has adapted to recent technological breakthroughs in order to realize the WKB2030 objectives.